STRATEGI PRA-PRODUKSI PROGRAM TELEVISI BERBASIS EDUKASI DI ERA KONVERGENSI MEDIA: STUDI KASUS PROGRAM TAU GAK SIH? DI TRANS7: A Case Study of the Tau Gak Sih? Program on TRANS7 - Rangga Permana; Safira Maulany (Jurnal Kajian Budaya dan Humaniora, 2025)
This article explores pre-production strategies in educational television programming, focusing on a case study of Tau Gak Sih?, a news magazine-style show aired on TRANS7. The program demonstrates how television can remain relevant amidst the rise of digital media by offering content that is informative, light, and visually engaging. The research employs a qualitative descriptive approach, combining participant observation and in-depth interviews. The study finds that pre-production stages—including idea research, field observation, pitching, permitting, and logistics—are crucial in producing episodes that align with the needs and preferences of younger audiences. The findings are analyzed through the lens of communication theories such as agenda setting, uses and gratifications, gatekeeping, and audience-centered production. The study concludes that a structured and adaptive pre-production process is essential to ensure the effectiveness and appeal of educational television programs in the media convergence era.